Benchmarking Cost of Milk Production in 46 Countries - Hemme, Torsten; Uddin, Mohammad Mohi; Ndambi, Oghaiki Asaah (Journal of Reviews on Global Economics, 2014)
The global dairy industry is facing challenges due to the extremely volatile milk price and a substantial increase of feed prices. The goal of this study, therefore, was to compare and benchmark the cost of milk production in 46 countries representing 87% of the world’s total milk production, using a standard method developed by the International Farm Comparison Network (IFCN). Two typical farms were selected per country; one average-sized and one larger farm. The cost of milk production in 2010 ranged from 16.91US-/100kg Energy Corrected Milk (ECM) in Armenia to 97.27 US-/100kg ECM in Switzerland, with cost differences mainly driven by the diversity in farming and feeding systems. Based on costs, world regions were categorized into four levels: 40-50 US- in the EU, Middle East and China; 30-40 US- in the USA, Brazil, CEEC and Oceania; <30 US- in Africa, Asia, South America; >60 US- in Austria, Norway, Switzerland and Canada. The major drivers for this variation were ranked as; purchased feed cost (the highest) followed by labor, land and machinery costs. Regression analyzes showed that costs were highly correlated milk yield and milk price but not to herd size.